Investigation of water substitution at RuII complexes by conceptual density function theory approach. Issue 17 (29th April 2022) - Ćoćić, Dušan; Petrović, Biljana; Puchta, Ralph; Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi
Abstract: In this paper, we investigated water exchange reactions and substitution of aqua Ru II complexes of general formula [Ru(terpy)(N^N)(H2 O)] 2+ (where N ^ N  = ethylenediamine (en), 1, 2‐(aminomethyl)pyridine (ampy) and 2, 2′‐bipyridine (bipy)) by ammonia and thioformaldehyde. These reactions were studied in detail by applying conceptual density functional theory. This approach enabled us to gain further insight into the underlying reaction mechanism at the microscopic level (involving only direct participants of the reaction, without the influence of the solvent) and to put the concept of reaction mechanism on a quantitative basis. The course of the chemical reaction along the reaction coordinate ξ, is rationalized in terms of reaction energy, force, dipole moment, and reaction electronic flux (REF). The results yield and characterize the significant influence of an intermolecular hydrogen bond formed between the entering and the spectator ligand to the overall energy barrier of the reactions. Abstract : Conceptual DFT calculations can be a powerful tool in providing a better understanding of the reaction mechanism at the microscopic level, without the interference of the solvent molecules. Throughout this paper these kind of calculations were used to investigate water substitution reactions on Ru II ‐aqua complexes. The results yield and characterize the significant influence of an intermolecular hydrogen bond formed between the entering and the spectator ligand to the overall energy barrier of the reactions.